2009
DOI: 10.1590/s0021-75572009000500013
|View full text |Cite
|
Sign up to set email alerts
|

Posição prona e diminuição da assincronia toracoabdominal em recém-nascidos prematuros

Abstract: IntroductionIn newborn infants, the configuration and complacency of the chest wall puts the respiratory system at a clear mechanical disadvantage with relation to adults. 1 The more horizontal position of the ribs makes the chest wall more rounded, rather than elliptical as is seen in adults, AbstractObjective: To assess the effect of prone and supine positions on breathing pattern variables, thoracoabdominal motion and peripheral oxygen saturation of hemoglobin of premature newborn infants recovering from r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 15 publications
(35 reference statements)
0
7
1
2
Order By: Relevance
“…Thus, the studied group was classified as eupneic. Another point that may explain the difference between the mean respiratory rate values of our study and those found by Oliveira et al 16 is that, despite the prematurity, our newborns did not suffer from respiratory distress syndrome.…”
Section: Variablescontrasting
confidence: 76%
See 2 more Smart Citations
“…Thus, the studied group was classified as eupneic. Another point that may explain the difference between the mean respiratory rate values of our study and those found by Oliveira et al 16 is that, despite the prematurity, our newborns did not suffer from respiratory distress syndrome.…”
Section: Variablescontrasting
confidence: 76%
“…The study by Leipälä et al 15 highlighted prone as the body position with the lowest mean respiratory rate for the group of preterm newborns dependent on oxygen therapy. In contrast, the study by Oliveira et al 16 showed that, in spontaneously breathing and clinically stable newborns after respiratory distress syndrome, the respiratory rate had a higher mean value in supine than in prone (74.22 vs. 68.67 rpm). In our study, the mean value in supine without elastic band was higher than in prone without elastic band (51.5 vs. 48.7 rpm), and supine and prone with elastic band (48.2 rpm vs. 48.4 rpm) were very similar to the value of prone without elastic band.…”
Section: Variablesmentioning
confidence: 80%
See 1 more Smart Citation
“…One of the important care for hospitalized NB in NICU is the decubitus change, that is, avoiding to keep them in only one posture. The correct positioning is beneficial both to the respiratory system, preventing accumulation of secretions, optimizing the function and thoracoabdominal biomechanics and facilitating lung expansion (8)(9)(10)(11)(12) as for the psychomotor and behavioral development and providing greater comfort preventing pressure ulcers (1,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…O DLE foi indicado por diversos estudos como o melhor posicionamento para se colocar a gestante na maca tradicional (Suonio et al, 1976;Ohashi et al, 2010;Rossi et al, 2011). (Guyton, 1999 Esses trabalhos foram realizados com recém-nascidos pré-termo (Oliveira et al, 2009), crianças submetidas a correção de escoliose idiopática (Brown et al, 2013), adultos jovens submetidos a cirurgias eletivas de hérnia de disco (Pelosi et al, 1995), pacientes obesos durante anestesia geral (Pelosi et al, 1996), adultos com síndrome da angústia respiratória aguda (SARA) ou com doenças pulmonares obstrutivas (Rival et al, 2011), adultos submetidos a circulação extracorpórea (Masuda et al, 2014) e pacientes que apresentam sintomas de agitação ao serem admitidos no hospital, sendo, por esse motivo, colocados na PP no setor de emergência médica (Savaser et al, 2013). Pela pesquisa realizada, verificou-se que esses importantes achados com a posição prona não abrangeram, no entanto, estudos sobre os parâmetros hemodinâmicos materno-fetais com várias gestantes sendo colocadas nesse posicionamento.…”
Section: Linha De Base Fetal Do Gg Nas Sequências 1 Eunclassified